2018
DOI: 10.1371/journal.pgen.1007840
|View full text |Cite
|
Sign up to set email alerts
|

The planar cell polarity protein VANG-1/Vangl negatively regulates Wnt/β-catenin signaling through a Dvl dependent mechanism

Abstract: Van Gogh-like (Vangl) and Prickle (Pk) are core components of the non-canonical Wnt planar cell polarity pathway that controls epithelial polarity and cell migration. Studies in vertebrate model systems have suggested that Vangl and Pk may also inhibit signaling through the canonical Wnt/β-catenin pathway, but the functional significance of this potential cross-talk is unclear. In the nematode C. elegans, the Q neuroblasts and their descendants migrate in opposite directions along the anteroposterior body axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…3F). Other potentially interesting factors were Vangl1, which modulates Wnt signalling and Trim25, an E3 ubiquitin ligase (Mentink et al, 2018;Munir, 2010) . Interestingly, this analysis only identified a subset of the previously proposed regulators.…”
Section: Identification Of Putative Xist Regulatorsmentioning
confidence: 99%
“…3F). Other potentially interesting factors were Vangl1, which modulates Wnt signalling and Trim25, an E3 ubiquitin ligase (Mentink et al, 2018;Munir, 2010) . Interestingly, this analysis only identified a subset of the previously proposed regulators.…”
Section: Identification Of Putative Xist Regulatorsmentioning
confidence: 99%
“…Why canonical Wnt-signaling activity has to be downregulated during early phases of neurogenesis remains to be determined. Given the evidence for crosstalk and functional antagonism between different Wnt-pathways (Baksh, Boland et al, 2007, Mentink, Rella et al, 2018, we speculate that sustained -catenin-signaling interferes with noncanonical Wnt-signaling pathways and their essential function in dendrite patterning and growth (Arredondo et al, 2019, Goncalves et al, 2016a, Schafer et al, 2015.…”
Section: Discussionmentioning
confidence: 91%
“…Fig. 5C) and a Vangl2 knock-out cell line (Mentink et al, 2018). With this antibody, we observed that VANGL2 expression was enriched in epithelial cells in both mouse and human embryonic LV ChP (Fig.…”
Section: Embryonic Chp Epithelium Expresses Various Wnt/pcp Componentsmentioning
confidence: 86%